#### Answer

$= 3$

#### Work Step by Step

$6+(-3)$
Recall positive sign times negative sign =negative sign
hence $6+(-3)$ is equivalent to $6-3$ and by simplification this gives you $3$
$6+(-3)=3$
$6 - 3 = 3$

Chegg costs money, GradeSaver solutions are free!

Published by
Prentice Hall

ISBN 10:
0133500403

ISBN 13:
978-0-13350-040-0

$= 3$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.